Repetition and international law - Werner, W. G. (Wouter G.), 1966- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
Acts of repetition abound in international law. Security Council Resolutions typically start by recalling, recollecting, recognising or reaffirming previous resolutions. Expert committees present restatements of international law. Students and staff extensively rehearse fictitious cases in presentations for moot court competitions. Customary law exists by virtue of repeated behaviour and restatements about the existence of rules. When sources of international law are deployed, historically contingent events are turned into manifestations of pre-given and repeatable categories. This book studies the workings of repetition across six discourses and practices in international law. It links acts of repetition to similar practices in religion, theatre, film and commerce. Building on the dialectics of repetition as set out by Søren Kierkegaard, it examines how repetition in international law is used to connect concrete practices to something that is bound to remain absent, unspeakable or unimaginable.
Introduction -- The eternal return of not quite the same : repetition and the sources of international law -- The law of receding origins : repetition and the identification of customary international law -- "Once upon a time, there was a story that began" : repetition in Security Council resolutions -- Say that again, please : repetition in the Tallinn manual -- Rehearsing rehearsing : repetition in international moot court competitions -- The unimaginable on screen : repetition in documentary films on trauma and atrocities.
Title from publisher's bibliographic system (viewed on 24 Jan 2022).
Keywords: International law -- Language; Repetition (Rhetoric); Rhetoric -- Political aspects